Antimicrobial susceptibility profiles of commensal Clostridium perfringens isolates from chickens in Hungarian poultry farms between 2022 and 2023 - Kerek, Ádám; Szabó, Ábel; Barnácz, Franciska; Csirmaz, Bence; Kovács, László; Jerzsele, Ákos (Frontiers in Veterinary Science, 2025)
IntroductionOne of the most pressing challenges of our time is the global spread of antimicrobial resistance (AMR). Regular surveillance studies are critical for advancing collaborative efforts between animal and public health sectors, aligning with the One Health concept.MethodsIn this study, we aimed to assess the antibiotic susceptibility of commensal Clostridium perfringens (C. perfringens) strains (n = 146) isolated from largescale poultry farms in Hungary, using minimum inhibitory concentration (MIC) determinations. Additionally, PCR was employed to investigate the presence of major and minor virulence factors.ResultsOur findings revealed a decrease in the efficacy of penicillin-based antibiotics, which are primary choices for treating C. perfringens-related infections, with resistance observed in 48.3% of isolates for penicillin and 20.7% for amoxicillin. Furthermore, virulence gene analysis identified 47 strains (32.2%) carrying the major beta toxin gene, one strain with the epsilon toxin gene (0.7%), 27 strains (18.5%) with the minor beta2 toxin gene, and four strains (2.7%) with the netB toxin gene.DiscussionThese results underscore the necessity of regular surveillance studies and highlight the significant role of commensal strains as reservoirs for sustaining resistance. Future research should include larger sample sizes to provide a more comprehensive understanding of resistance dynamics. Additionally, the genetic basis of resistance in multidrug-resistant strains should be elucidated using next-generation sequencing, enabling targeted interventions to address this growing concern.